Analisis Faktor Penghambat dalam Pelaksanaan Program Tahfidz di MI Terpadu Tahfidzul Qur’an Al-Ma’shum (MITTQUM) Surakarta - Kinesti, Rakanita Dyah Ayu; Arum, Deby Nadiva Sekar; Lutfin, Windy Faeroza; Nida, Fajria Khoirin (Lembaga Yasin AlSys, 2023)
Madrasah Ibtidaiyah Terpadu Tahfizhul Qur'an Al-Ma'shum (MITTQUM) is an educational institution unit under the auspices of the Ar-Rahman Surakarta Foundation since 2011. MITTQUM is one of the pioneer madrasas for the tahfizhul Qur'an program in the city of Solo. The implementation of the tahfidz program at Integrated MI Al Ma'sum Surakarta involves various aspects that aim to create a conducive and systematic learning environment for students to memorize the Al-Qur'an. In addition, educators or teachers at MI also need to pay attention to the inhibiting factors for evaluation materials so that they can develop better. The method used in this study is a qualitative method with a descriptive approach. In seeking information about this research, the authors used interviews, observation, and documentation. The result of this study is that the program planning is based on efforts to improve students' abilities. There are 2 superior programs for Tahfidzul Qur'an in this madrasah, namely the regular program (memorization target of 6 juz) and the kuttab program (target memorization of 15 juz). The tahfidzul qur'an program activities include: Recitations, Ziyadah, Muraja'ah PR Halaqah, Juz'iyah Test. Factors that can hinder the tahfidz program at MITTQUM are due to the lack of variety of learning methods, excessive educator workload, lack of support and facilities in implementing tahfidz, excessive dependence on the teacher as the only teaching tool, lack of parental role in helping students memorize, lack of coordination of teacher communication with parents, and the psychological condition of students is uncertain.